Admixture mapping of peripheral artery disease in a Dominican population reveals a putative risk locus on 2q35 - Cullina, Sinead; Wojcik, Genevieve L.; Shemirani, Ruhollah; Klarin, Derek; Gorman, Bryan R.; Sorokin, Elena P.; Gignoux, Christopher R.; Belbin, Gillian M.; Pyarajan, Saiju; Asgari, Samira; Tsao, Philip S.; Damrauer, Scott M.; et al. (Frontiers in Genetics, 2023)
Peripheral artery disease (PAD) is a form of atherosclerotic cardiovascular disease, affecting ~8 million Americans, and is known to have racial and ethnic disparities.  PAD has been reported to have significantly higher prevalence in African Americans (AAs) compared to non-Hispanic European Americans (EAs). Hispanic/Latinos (HLs) have been reported to have lower or similar rates of PAD compared to EAs, despite having a paradoxically high burden of PAD risk factors, however recent work suggests prevalence may differ between sub-groups. Here we examined a large cohort of diverse adults in the BioMe biobank in New York City (NYC). We observed the prevalence of PAD at 1.7% in EAs vs 8.5% and 9.4% in AAs and HLs, respectively; and among HL sub-groups, at 11.4% and 11.5% in Puerto Rican and Dominican populations, respectively. Follow-up analysis that adjusted for common risk factors demonstrated that Dominicans had the highest increased risk for PAD relative to EAs (OR=3.15 (95% CI 2.33-4.25), P<6.44x10-14). To investigate whether genetic factors may explain this increased risk, we performed admixture mapping by testing the association between local ancestry (LA) and PAD in Dominican BioMe participants (N=1,940) separately for European (EUR), African (AFR) and Native American (NAT) continental ancestry tracts. We identified a NAT ancestry tract at chromosome 2q35 that was  significantly associated with PAD  (OR=2.05 (95% CI 1.51-2.78), P<4.06x10-6) with 22.5% vs 12.5% PAD prevalence in heterozygous NAT tract carriers versus non-carriers, respectively. Fine-mapping at this locus implicated tag SNP rs78529201 located within a long intergenic non-coding RNA (lincRNA) LINC00607, a gene expression regulator of key genes related to thrombosis and extracellular remodeling of endothelial cells, suggesting a putative link of the 2q35 locus to PAD etiology. In summary, we showed how leveraging health systems data helped understand nuances of PAD risk across HL sub-groups and admixture mapping approaches elucidated a novel risk locus in a Dominican population.